2011
DOI: 10.1186/2191-219x-1-25
|View full text |Cite
|
Sign up to set email alerts
|

Use of [18F]FDOPA-PET for in vivo evaluation of dopaminergic dysfunction in unilaterally 6-OHDA-lesioned rats

Abstract: BackgroundWe evaluated the utility of L-3,4-dihydroxy-6-[18F]fluoro-phenylalanine ([18F]FDOPA) positron emission tomography (PET) as a method for assessing the severity of dopaminergic dysfunction in unilaterally 6-hydroxydopamine (6-OHDA)-lesioned rats by comparing it with quantitative biochemical, immunohistochemical, and behavioral measurements.MethodsDifferent doses of 6-OHDA (0, 7, 14, and 28 μg) were unilaterally injected into the right striatum of male Sprague-Dawley rats. Dopaminergic functional activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 58 publications
2
40
0
Order By: Relevance
“…Common tracers are [ 18 F] l -3,4-dihydroxyphenylalanine (DOPA), that give an estimate of dopamine synthesis and radioligands with affinity for proteins important for the dopaminergic transmission (e.g., DAT, D 2 receptor, vesicular monoamine transporter type 2). In a recent study, Kyono et al [25] showed that PET detection of striatal uptake of [ 18 F]FDOPA, after inhibition of aromatic l -amino acid decarboxylase and catechol- O -methyltransferase, is significantly correlated to striatal dopamine levels in the partially 6-OHDA-lesioned rat brain. They did four-site striatal 6-OHDA lesions of a total of 7, 14, or 28 μg 6-OHDA.…”
Section: Discussionmentioning
confidence: 99%
“…Common tracers are [ 18 F] l -3,4-dihydroxyphenylalanine (DOPA), that give an estimate of dopamine synthesis and radioligands with affinity for proteins important for the dopaminergic transmission (e.g., DAT, D 2 receptor, vesicular monoamine transporter type 2). In a recent study, Kyono et al [25] showed that PET detection of striatal uptake of [ 18 F]FDOPA, after inhibition of aromatic l -amino acid decarboxylase and catechol- O -methyltransferase, is significantly correlated to striatal dopamine levels in the partially 6-OHDA-lesioned rat brain. They did four-site striatal 6-OHDA lesions of a total of 7, 14, or 28 μg 6-OHDA.…”
Section: Discussionmentioning
confidence: 99%
“…4--6,8 Although an unchanged k ref in mild lesions is in keeping with predictions based on the characterization of the 6-OHDA model via non-PET methods, it disagrees with some PET-based reports of a reduced k ref (or K i ) in lesioned nonhuman primates 8 and 6-OHDA lesioned rats. 9 This discrepancy may be explained by the disease-dependent negative bias introduced into k ref when calculated by the traditional (nonextended) Patlak graphical analysis which neglects k loss . This bias depends on k loss , being most apparent in species where k loss is large (such as the rat), and/ or in the diseased state.…”
Section: Discussionmentioning
confidence: 99%
“…Such methodology has been successfully applied in humans 1--5 and nonhuman primates 6--8 but only limited studies have been reported in the rat. 9 Given that rodent models are critical in medical research, it is important to develop imaging methodology in these species, and for specific biological readouts to be verified. A number of diseases are associated with changes or dysfunction in the dopaminergic system, most notably Parkinson's disease (PD).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, [ 18  F]FDOPA PET has been used in the study of mouse [7,8] and rat [9,10] models of Parkinson's disease (PD). The increasing availability of transgenic rodent models of PD which may recapitulate the cardinal features of the disease, including disease progression, has spurred new interest in imaging the dopaminergic system of rodents.…”
Section: Introductionmentioning
confidence: 99%